2018
DOI: 10.3768/rtipress.2018.op.0048.1802
|View full text |Cite
|
Sign up to set email alerts
|

Universal Screening of Young Children for Developmental Disorders: Unpacking the Controversies

Abstract: This PDF document was made available from www.rti.org as a public service of RTI International. More information about RTI Press can be found at http://www.rti.org/rtipress. RTI International is an independent, nonprofit research organization dedicated to improving the human condition by turning knowledge into practice. The RTI Press mission is to disseminate information about RTI research, analytic tools, and technical expertise to a national and international audience. RTI Press publications are peerreviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Universal screening refers to a process using developmental screening tools with all children and families within a setting, regardless of risk status (e.g., a screening tool is used to assess all toddlers in a childcare center at 16 months) (Wallace, 2018). Universal screening identifies children with delayed development as early as possible in a systematic prevention approach to mitigating developmental deficits.…”
Section: Universal Screening For Language and Social-emotional Develo...mentioning
confidence: 99%
“…Universal screening refers to a process using developmental screening tools with all children and families within a setting, regardless of risk status (e.g., a screening tool is used to assess all toddlers in a childcare center at 16 months) (Wallace, 2018). Universal screening identifies children with delayed development as early as possible in a systematic prevention approach to mitigating developmental deficits.…”
Section: Universal Screening For Language and Social-emotional Develo...mentioning
confidence: 99%
“…Developmental screening involves the use of brief questionnaires and/or standardized tools, used at a designated point in time, to assist in the identification of children who are vulnerable to developmental difficulty. The purpose of developmental screening is to identify children at increased risk of a disorder and who need referral for further in-depth diagnostic assessment (7,8). Universal screening is recommended when there is a tool sufficiently accurate to ensure confidence in identifying children truly at risk from all children in a certain age group of the population regardless of symptomatology (8), for example, with infant hearing screening.…”
Section: Developmental Surveillance and Screeningmentioning
confidence: 99%
“…The purpose of developmental screening is to identify children at increased risk of a disorder and who need referral for further in-depth diagnostic assessment (7,8). Universal screening is recommended when there is a tool sufficiently accurate to ensure confidence in identifying children truly at risk from all children in a certain age group of the population regardless of symptomatology (8), for example, with infant hearing screening. Neither universal nor targeted speech and language screening are currently recommended; two systematic reviews conducted for the US Preventative Services Task Force (4,9), concluded there was inadequate evidence on the accuracy of screening instruments for speech and language delay.…”
Section: Developmental Surveillance and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The Task Force therefore did not support routine screening in asymptomatic children ( 11 ). This has raised concerns in the professional community who believe in the benefits of routine screening ( 12 ). However, it is undeniable that another contributing factor for the recommendation of the Task Force was that screening tools for language disorder vary greatly in design and construct resulting in the variability in identification accuracy.…”
Section: Introductionmentioning
confidence: 99%